If α , β are the roots of the equation x 2 − p ( x + 1 ) − c = 0 (where p , c are real numbers ,not equal to zero) then α 2 + 2 α + c α 2 + 2 α + 1 + β 2 + 2 β + c β 2 + 2 β + 1 is equal to:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Well, we also have to ensure that the denominator is non-zero right?
Well done ! : )
Can you please explain me i , i i
Log in to reply
As α and β are the roots of the given equation , when put in place of x , they make the equation zero.
you could also add the first two equations and get α + β + α β = c a n d s u b s t i t u t e i t .
Problem Loading...
Note Loading...
Set Loading...
F r o m V i e t a ′ s R u l e , α + β = p α β = − ( p + c ) T h e g i v e n e q u a t i o n h a s α a n d β a s i t s r o o t s . H e n c e α 2 − p ( α + 1 ) = c − − − − − − − − − − ( i ) β 2 − p ( β + 1 ) = c − − − − − − − − − − ( i i ) α 2 + 2 α + c α 2 + 2 α + 1 + β 2 + 2 β + c β 2 + 2 β + 1 = α 2 + 2 α + α 2 − p α − p α 2 + 2 α + 1 + β 2 + 2 β + β 2 − p β − p β 2 + 2 β + 1 = 2 α ( α + 1 ) − ( α + β ) ( α + 1 ) ( α + 1 ) 2 + 2 β ( β + 1 ) − ( β + 1 ) ( α + β ) ( β + 1 ) 2 = ( α + 1 ) ( α − β ) ( α + 1 ) 2 + ( β + 1 ) ( β − α ) ( β + 1 ) 2 = ( α − β ) ( α + 1 ) + ( β − α ) ( β + 1 ) = ( α − β ) ( α + 1 ) − ( α − β ) ( β + 1 ) = α − β α − β = 1